2020
DOI: 10.1016/j.jid.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor FOXN1 Regulates Skin Adipogenesis and Affects Susceptibility to Diet-Induced Obesity

Abstract: FOXN1, a transcription factor expressed in the epidermis, regulates keratinocyte differentiation and participates in skin wound healing. In this study, we explored the impact of FOXN1 insufficiency on diet-stimulated weight gain and dermal white adipose tissue regulation in the intact and wounded skin of FOXN1 eGFP/þ (heterozygotes, FOXN1-insufficient) mice in the context of age and diet. The results showed that on a high-fat diet, FOXN1 eGFP/þ mice gained significantly less body weight than their FOXN1 þ/þ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 52 publications
1
44
0
6
Order By: Relevance
“…regulates the adipogenic potential of the skin (dermal white adipose tissues; dWAT), thereby contributing to the skin wound healing process (Walendzik et al, 2019). The present data suggest that Foxn1 may modulate skin homeostasis (keratinocyte proliferation/differentiation) and the skin response to wounding through the regulation of the skin response to different (normoxia vs hypoxia) levels of oxygenation.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…regulates the adipogenic potential of the skin (dermal white adipose tissues; dWAT), thereby contributing to the skin wound healing process (Walendzik et al, 2019). The present data suggest that Foxn1 may modulate skin homeostasis (keratinocyte proliferation/differentiation) and the skin response to wounding through the regulation of the skin response to different (normoxia vs hypoxia) levels of oxygenation.…”
Section: Discussionmentioning
confidence: 64%
“…Our previous study revealed that Foxn1 is one of the key regulators in the skin wound healing process (Gawronska-Kozak et al, 2016;M. M. Kopcewicz et al, 2017;Walendzik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence detection and colocalization of Foxn1 and Trx-1 were performed on skin samples from young Foxn1::Egfp transgenic mice at day 3 postwounding. 41 The samples were fixed in 4% PFA for 2 hours, washed in 0.1 M PB (Sigma-Aldrich) overnight at 4°C and stored in 18% sucrose (Chempur, Poland)/0.1 M PB solution prior to cryosectioning. Immunofluorescence assays were performed with the following primary antibodies: anti-Trx-1 (1:50, Cat# 24295, Cell Signaling) and anti-eGFP (1:400, Cat# 6673, Abcam).…”
Section: Histologymentioning
confidence: 99%
“…Members of the CCAAT/enhancer-binding protein (C/EBP) family and the preceding peroxisoe proliferator-activated receptors (PPARs) family are the two most critical transcription factors associated to adipogenic-speci c program, among which C/EPBβ plays an essential role [8][9][10]. During A-MSCs adipo-differentiation, activated C/EBPβ triggers transcription of C/EPBα and PPARγ, which in turn coordinately activate genes, such as fatty acid-binding proteins (FABPs), fatty acid transport proteins (FATPs), whose expression produces for terminal adipocyte [11,12].…”
Section: Introductionmentioning
confidence: 99%